In search of lost meaning : the new Eastern Europe - Michnik, Adam (University of California Press, 2011)
In this new collection of essays, Adam Michnik--one of Europe's leading dissidents--traces the post-cold-war transformation of Eastern Europe. He writes again in opposition, this time to post-communist elites and European Union bureaucrats. Composed of history, memoir, and political critique, In Search of Lost Meaning shines a spotlight on the changes in Poland and the Eastern Bloc in the post-1989 years. Michnik asks what mistakes were made and what we can learn from climactic events in Poland's past, in its literature, and the histories of Central and Eastern Europe. He calls attention to pivo.